2005
DOI: 10.1128/aem.71.10.6193-6198.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phylum- and Class-Specific PCR Primers for General Microbial Community Analysis

Abstract: Amplification of a particular DNA fragment from a mixture of organisms by PCR is a common first step in methods of examining microbial community structure. The use of group-specific primers in community DNA profiling applications can provide enhanced sensitivity and phylogenetic detail compared to domain-specific primers. Other uses for group-specific primers include quantitative PCR and library screening. The purpose of the present study was to develop several primer sets targeting commonly occurring and impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 41 publications
0
78
0
Order By: Relevance
“…In silico analysis of the group-specific PCR primers Blackwood et al (2005) used ARB to develop five group-specific primers including primers for four of the groups of bacteria investigated in this study. Ashelford et al (2002) compared in detail the PRIMROSE and ARB programs and concluded that in many cases it was possible to identify better oligonucleotide probes (judged by in silico analysis) using PRIMROSE rather than ARB.…”
Section: Resultsmentioning
confidence: 99%
“…In silico analysis of the group-specific PCR primers Blackwood et al (2005) used ARB to develop five group-specific primers including primers for four of the groups of bacteria investigated in this study. Ashelford et al (2002) compared in detail the PRIMROSE and ARB programs and concluded that in many cases it was possible to identify better oligonucleotide probes (judged by in silico analysis) using PRIMROSE rather than ARB.…”
Section: Resultsmentioning
confidence: 99%
“…In the first round of PCR, the primers F984GC (5'gc-AACGCGAAGAACCTTAC 3')/R1492 (5' TACGG(C/T)TA CCTTGTTACGACTT 3'), F243 (5' GGATGAGCCCGCGGCCTA 3')/R1492 and BLS342F (5' CAGCAGTAGGGAATCTTC 3')/R1392 (5' ACGGGCGGTGTGTACA 3') were used to amplify 16S rDNA gene regions specific to Bacteria domain, Actinobacteria and Firmicutes phyla, respectively [28,29]. Primer F984GC contained a GCclamp at the 5'end [28].…”
Section: Amplification and Denaturing Gradient Gel Electrophoresis (Dmentioning
confidence: 99%
“…Recently, many efforts have been made to develop phylum-or higher taxonomic group-specific PCR primers (Blackwood et al, 2005;Dopheide et al, 2008;Scheckenbach et al, 2010;Stoeck et al, 2009). The main problem encountered in these previous studies is a difficulty in designing higher taxonomic groupspecific primers that discriminate between target groups among all eukaryotes that exist in an environmental sample.…”
Section: Introductionmentioning
confidence: 99%
“…However, predominant organisms or ones possessing genes with sequences preferentially amplified by PCR will be detected before to rare species because the eukaryotic organism communities in most environmental samples are too complex and diverse to be thoroughly analyzed in a single study. For this reason, rare species or small taxonomic groups will not be evenly represented in the sampling data even if mass sequencing methods are used (Blackwood et al, 2005;Nolte et al, 2010;Scheckenbach et al, 2010;Shanks et al, 2011). Rare species or minor taxonomic groups, however, may be more important than quantitatively dominant species when analyzing community structures due to their narrow range of distribution and susceptibility to minute habitat alterations or ecological disturbances (Blackwood et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation